Examining the Impact of Trust on Social Media Networks (A study on people living in Malaysia) - Onyemeh, Ngozi Celestina (2011)
According to Accenture 2010 Global Consumer Survey; Social media has be- come the facilitator or the enabler of interaction between diverse digital net- works and mobile devices and is radically accelerating the exchange of cus- tomer opinions. Exchanges through this media are steadily being acclaimed as word of mouth impacting consumer decision as consumers communicate fa- vourable experience and unfavourable experiences with different products. Trust, on the other hand, is emerging as a critical influencer of consumer be- haviour suggesting that trust building among a company’s customer base rep- resents a large opportunity. Since most exchanges are going on in social media, which represents a shift from the traditional method of communication, the role trust plays becomes a subject of interest. Organisations now have a need to ef- fectively manage their social media strategies and practices. To examine the impact of trust, its antecedents and its relationship with social media, a survey was conducted in this research project with 262 respondents participating. Data analysis using SPSS showed that integrity, concern, aligned values and communication which are termed high level antecedents, are strong predictors of trustworthiness which ultimately leads to trust. The low level an- tecedents namely consistency, competence, network effect and customer em- powerment orientation did not demonstrate they could on their own reduce the risk and uncertainty which is considered inherent in trust. Nonetheless, their impact was not completely eliminated but was felt through the high level ante-cedents. Intended users of this study should be aware of the outlined limitations of this research as they may have influenced the findings and ultimately the analysis and the conclusions drawn. However, it should be noted that the findings are in line with earlier researches done by other renowned authors. It is hoped that future research on this subject of interest will strive to overcome the shortcom- ings that have been mentioned.